2014
DOI: 10.1589/jpts.26.349
|View full text |Cite
|
Sign up to set email alerts
|

Electrocortical Analysis of Patients with Intercostobrachial Pain Treated with TENS after Breast Cancer Surgery

Abstract: [Purpose] Among the physical therapeutic procedures to decrease pain, there is transcutaneous electrical neural stimulation (TENS). There is no consensus about its efficacy for oncological patients, especially for post-mastectomy pain and eletrocortical changes in somatosensory areas. The aim of this study was to analyze acute electrocortical changes after TENS treatment of patients with intercostobrachial post mastectomy pain. [Subjects] Eighteen patients were divided into acupuncture (A) and burst (B) group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 26 publications
0
22
0
2
Order By: Relevance
“…Electrical stimulation is a popular treatment used by physiotherapists for muscle strengthening, endurance, spasticity management, pain control, circulation promotion and edema control 1 , 2 , 3 , 4 , 5 ) . Transcutaneous electrical nerve stimulation (TENS) and interferential current (IFC) are widely used for relief of chronic and acute pain 6 , 7 , 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Electrical stimulation is a popular treatment used by physiotherapists for muscle strengthening, endurance, spasticity management, pain control, circulation promotion and edema control 1 , 2 , 3 , 4 , 5 ) . Transcutaneous electrical nerve stimulation (TENS) and interferential current (IFC) are widely used for relief of chronic and acute pain 6 , 7 , 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2014) found a reduction in intercostobrachial pain among breast cancer survivors following the administration of transcutaneous electrical nerve stimulation. Fernández-Lao et al (2012) found an increase in the pressure pain threshold using a protocol involving endurance, stretching, strengthening and massage.…”
Section: Discussionmentioning
confidence: 96%
“…However, the preliminary aim of the present study is not to produce pain but find out the effects of TENS application, which is a device mostly used in the treatment of pain. There are few studies which have analyzed the effect of TENS with EEG (Olson, 1993;Urasaki et al, 1998;Hoshiyama & Kakigi, 2000;Silva et al, 2014;Pierleoni, Gizdulich & Paoletti, 2011;Ebrahimian et al, 2018). In these studies EEG was recorded to find out the pre and post-treatment effects of TENS application in different groups of subjects.…”
Section: Introductionmentioning
confidence: 99%